2000
DOI: 10.1021/jp002167k
|View full text |Cite
|
Sign up to set email alerts
|

The Siting of Ti in TS-1 Is Non-Random. Powder Neutron Diffraction Studies and Theoretical Calculations of TS-1 and FeS-1

Abstract: We present the first direct evidence of non random siting of Ti and Fe in TS-1 and FeS-1, nanoporous metallosilicate selective oxidation catalysts of MFI topology. This was accomplished by using Rietveld analysis of powder neutron diffraction data and exploiting the differences in neutron scattering lengths between Ti or Fe and Si. Previous spectroscopic, X-ray diffraction, and computational approaches have suggested a random substitution of Ti and Fe ions among the 12 crystallographically distinct Si sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 38 publications
6
93
1
Order By: Relevance
“…Moreover, the incorporation of heteroatoms occurred through kinetically controlled process during the early stage of synthesis, and it has been proved that the computations based on thermodynamics failed to predict the experimental observed citing of Ti and Fe in zeolites. 30 We believe that such a behavior should also be valid to the process of Al substitution in ZSM-5 zeolite. Recently, Olson et al 17 have carried out x-ray diffraction experiments for extra-framework cesium cations and reached the conclusion that T4, 7, 11, and 12 would be the possible sites for Al substitution.…”
Section: A Location Of La"oh…mentioning
confidence: 67%
“…Moreover, the incorporation of heteroatoms occurred through kinetically controlled process during the early stage of synthesis, and it has been proved that the computations based on thermodynamics failed to predict the experimental observed citing of Ti and Fe in zeolites. 30 We believe that such a behavior should also be valid to the process of Al substitution in ZSM-5 zeolite. Recently, Olson et al 17 have carried out x-ray diffraction experiments for extra-framework cesium cations and reached the conclusion that T4, 7, 11, and 12 would be the possible sites for Al substitution.…”
Section: A Location Of La"oh…mentioning
confidence: 67%
“…[51][52][53] Thus, the lattice O rather than the lattice Ti III radicals are crucial for the activation of alkane C À H bonds. The T7 site was chosen for the reactivity studies on TS-1 zeolite, [12][13][24][25] and the optimized structures are given in Figure S9 of the Supporting Information. The activation of a methane CÀH bond by the Ti7 III site requires an energy barrier of 17.8 kJ mol…”
Section: Resultsmentioning
confidence: 99%
“…There is abundant information on the distributions of triand tetravalent ions (e.g., B, Al, and Ti) in MFI-type zeolites. [16][17][18][19][20][21][22][23][24][25][26][27] Recently, the Al locations in MCM-22 zeolite were studied by Corma et al and our group. [28][29][30] It was found that these ions are not equally distributed among the various T sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T sites which contain Ti are T3, T8, and T10, whereas all other sites are essentially free of Ti [ 96 ]. In a different neutron powder diffraction analysis [ 97 ], the authors suggested that T3, T7, T8, T10 or T6, T7, and T11, respectively, are preferentially occupied by Ti, with T10 showing only weak evidence [ 98 ]. However, the authors did not use samples isotopically enriched in Ti isotopes and, thus, were not able to differentiate contributions due to structural defects from those of Ti occupancy at specifi c T sites.…”
Section: Redox Sites: Fe and Ti In Mfi-type Frameworkmentioning
confidence: 93%